Improvement of Fluid Simulation Runtime of Smoothed Particle Hydrodynamics by Using Graphics Processing Unit (GPU) - Wahyu Srigutomo; Ruddy Kurnia; Suprijadi Suprijadi (Journal of ICT Research and Applications, 2017)
This study concerns an implementation of smoothed particle hydrodynamics (SPH) fluid simulation on a graphics processing unit (GPU) using the Compute Unified Device Architecture's (CUDA) parallel programming. A bookkeeping method for the neighbor search algorithm was incorporated to accelerate calculations. Based on sequence code profiling of the SPH method, particle interaction computation "“ which comprises the calculation of the continuity equation and the momentum conservation equation "“ consumes 95.2% of the calculation time. In this paper, an improvement of the calculation is proposed by calculating the particle interaction part on the GPU and by using a bookkeeping algorithm to restrict the calculation only to contributed particles. Three aspects are addressed in this paper: firstly, speed-up of the CUDA parallel programming computation as a function of the number of particles used in the simulation; secondly, the influence of double precision and single precision schemes on the computational acceleration; and thirdly, calculation accuracy with respect to the number of particles. Scott Russell's wave generator was implemented for a 2D case and a 3D dam-break. The results show that the proposed method was succesfull in accelerating the SPH simulation on the GPU.